2024
DOI: 10.1021/acs.chemmater.4c00769
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Catalysis in a Crystalline Framework with Templated Acid–Base Sites

Devin S. Rollins,
Jackson Geary,
Kamaya Ronning
et al.

Abstract: Nature uses weakly basic residues in conjunction with weakly acidic residues to catalyze challenging heterolytic bond transformations. Here, we show that these cooperative effects can be replicated in a metal−organic framework (MOF) containing bifunctional Brønsted acid−base sites. Using a templating strategy, we show that the colocalization of acid and base sites is key to catalytic activity. Specifically, a thermolabile cross-linker containing tertiary ester and tertiary carbamate linkages is used to tether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…To address this challenge, we recently reported a strategy to introduce closely spaced pairs of functional groups within MOF pores, irrespective of functional group loading. ,, We first showed that thermolabile tertiary ester-based cross-linkers can be used to template pairs of carboxylic acids ∼7 Å apart down the pore channels of Mg 2 dotpdc (dotpdc 4– = 4,4″-dioxido-[1,1′:4′,1″-terphenyl]-3,3″-dicarboxylate), a mesoporous framework with one-dimensional hexagonal channels. We later developed tertiary carbamate-based cross-linkers that, upon thermolysis, reveal pairs of templated amines (Figure a) .…”
Section: Synthetic Strategiesmentioning
confidence: 99%
“…To address this challenge, we recently reported a strategy to introduce closely spaced pairs of functional groups within MOF pores, irrespective of functional group loading. ,, We first showed that thermolabile tertiary ester-based cross-linkers can be used to template pairs of carboxylic acids ∼7 Å apart down the pore channels of Mg 2 dotpdc (dotpdc 4– = 4,4″-dioxido-[1,1′:4′,1″-terphenyl]-3,3″-dicarboxylate), a mesoporous framework with one-dimensional hexagonal channels. We later developed tertiary carbamate-based cross-linkers that, upon thermolysis, reveal pairs of templated amines (Figure a) .…”
Section: Synthetic Strategiesmentioning
confidence: 99%